Analisis Kinerja Keuangan Bank Tabungan Negara (Persero) Tbk. Berdasarkan Laporan Keuangan Tahun 2022-2023 (Lembaga Pengembangan Kinerja Dosen, 2025)
Financial performance assessment is an important aspect in evaluating the condition and sustainability of a company, including in the banking sector. This study aims to analyze the financial performance of Bank Tabungan Negara (Persero) Tbk. (BTN) based on the 2021 and 2022 financial statements. The analysis was carried out using several key financial ratios, such as liquidity, profitability, solvency, and efficiency ratios. The results of the study show that BTN experienced changes in several financial indicators that reflect the bank's response to economic dynamics and banking sector policies during that period. Through this analysis, a picture of BTN's financial strengths and weaknesses is obtained which can be used as a reference in strategic decision making for management as well as consideration for investors and other stakeholders.